Perfluoroalkyl substances in precipitation from the Tibetan Plateau during monsoon season: Concentrations, source regions and mass fluxes. (November 2021) - Chen, Mengke; Wang, Chuanfei; Gao, Ke; Wang, Xiaoping; Fu, Jianjie; Gong, Ping; Wang, Yongjie
Abstract: Atmospheric wet deposition is an important process for the occurrence of perfluoroalkyl substances (PFASs) in polar/remote mountain regions; however, there are limited data on PFASs in precipitation from the Tibetan Plateau (TP). Precipitation (rain from May to October 2017) was therefore collected across the TP to investigate the concentrations, composition profiles, sources, and fluxes of perfluoroalkyl acids (PFAAs). The average ∑PFAA concentrations ranged from 212.3 pg L −1 to 547.7 pg L −1, and perfluoroalkyl carboxylic acids (PFCAs) accounted for 87% of the measured PFAAs (mean value). Significant positive associations ( p  < 0.05) were found for most PFCAs in the southeast TP, indicating that they may come from similar sources. The monthly PFAA deposition flux ranged from 12.6 to 68.9 ng m −2 month −1, decreasing from east to west. As climate of the eastern TP is controlled mainly by the Indian monsoon, indicating that the Indian monsoon plays an important role in delivering PFAAs to the TP. PCA (principal component analysis) combined with back-trajectory analysis was used to estimate the atmospheric transport pathways, and the PSCF (potential source contribution function) model was applied to define the potential source regions of individual PFAAs. The results suggested that northeast India, Bangladesh, and southern Nepal are the potential sources of C4–C7 PFCAs; C8–C10 PFCAs are more influenced by emissions from southern Nepal and Bhutan; while the source regions of long-chain PFCAs (C11–C12) can be attributed to northern India and Pakistan. Specifically, PFOS (perfluorooctane sulfonic acid) has a local contribution from the central TP. Highligts: The mean PFAA concentrations are higher in the eastern Tibetan Plateau (TP). The ∑PFAAs flux (12.6–68.9 ng m −2 month −1 ), decreasing from east to west of the TP. South Asia offers the important sources of PFAAs on the TP, especially for PFCAs. The Indian monsoon plays an important role in delivering PFAAs to the TP in summer.